Science and Technology Policy in Assessments of Russian Scientists - Tatiana Kuznetsova (Foresight and STI Governance, 2008)
The Russian science is already for a long time suffers the increasing lack of people that results in ageing of scientific personnel, falling prestige of related activities, worsening quality of scientific results etc. In this case it is very interesting to know how the scientists themselves estimate opportunities, constraints and prospects of modernization of state science policy, adequacy and efficiency of its instruments. The paper discusses preliminary results of survey of working environment and attractiveness of scientific career that was undertaken in 2007 by the HSE Institute for Statistical Studies and Economics of Knowledge.